1947
DOI: 10.1111/j.1748-1716.1947.tb00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of Salyrgan on the Absorption of Water and Colloid from Joints.

Abstract: The oncotic pressure of this solution, calculated according to ADAIR (1928) and corrected for temperature (38" C) according t o WELLS et al. (1935), is 270 mm of water. The following formulas have been used: Oncotic pressure of the hemoglobin solution = __ -p (mm of H,o); V -B 100 ___. B = 2.54; p1 = p ; ; t* t and t,: K = 3700; V = Hb conc. in g per cent' absolute temperatures in degrees of C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1949
1949
1969
1969

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The flow-pressure curve was a straight line. Similar findings concerning the resistance to flow of normal and edematous synovial membranes have been reported (EDLUND 1949).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The flow-pressure curve was a straight line. Similar findings concerning the resistance to flow of normal and edematous synovial membranes have been reported (EDLUND 1949).…”
supporting
confidence: 86%
“…These values, as well as the pressure level of the breaking point, do not differ significantly from those earlier published (EDLUND 1949). I n twenty-six operated animals with heart failure there was no breaking point in any of the joints investigated.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…In the studies presented here we have shown that alloxan causes the breaking-point to disappear when the measurements are made in normal joints and to reappear when they are made in joints subjected to burns. In these respects alloxan has the same effect as desoxycorticosterone acetate (EDLUND et al 1955;EDLUND 1949). Animals subjected to intraarticular burns by the method used here show histologically a slight second-degree burn in the synovial membrane (EDLUND 1949).…”
Section: Discussionmentioning
confidence: 85%
“…It might be argued that the reappearance of the breaking-point in the burned alloxan animals can be due to causes other than an anti-oedematous effect of the drug, since we have no histological controls for the degree of oedema. The oedematous reaction, however, cannot possibly have been enhanced by alloxan, because even in more pronounced oedema the pressure-flow curve is a single straight line (EDLUND 1949).…”
Section: Discussionmentioning
confidence: 99%